Textbook on administrative law - Leyland, Peter (Oxford University Press, 2005)
his text is written for anyone studying administrative law who requires a concise and readable textbook. It is specifically directed at LLB and CPE students, as well as those approaching the subject for the first time at undergraduate or postgraduate level, including non-law students in related fields